A review of tobacco smoking and smoking cessation practices among physicians in China: 1987–2010. Issue 1 (15th December 2011) - Abdullah, Abu S; Qiming, Feng; Pun, Vivian; Stillman, Frances A; Samet, Jonathan M
Abstract : Background: Tobacco use by physicians represents a significant barrier in promoting smoking cessation through physician interventions. To assess the need for and nature of smoking cessation services among physicians in China, a detailed literature review was conducted. Methods: A literature review of studies published, in Chinese or in English, between 1987 and 2010, was carried out. The Medline, PubMed and Wanfang Data (a Chinese literature search database) electronic databases were searched for published studies. Results: It was found that the overall current smoking prevalence among Chinese physicians ranged from 14% to 64% (men: 26% to 61%; women: 0% to 19%). There were significant gender differences in the smoking prevalence across studies with men smoking more than women. Though inconsistent, there were variations in smoking rates by professional posts and medical specialty. The quit smoking rates ranged from 5% to 14% across studies, with a higher rate among female physicians. Asking about smoking status or advising patients to quit smoking was not common practice among the physicians. Conclusions: The results of this review suggest that while smoking habits of Chinese physicians vary among studies and across physicians in different specialties; prevalence rates tend to be higher than in physicians in the developed countries. Quitting rates were low among Chinese physicians, and the delivery of advice on quitting smoking was not common across the studies. Strategies to improve Chinese physicians' engagement in smoking cessation should address multiple factors including tobacco use and quitting practices among the physicians, their training needs and awareness of their professional responsibility with a healthcare system change approach.